2016
DOI: 10.1016/j.redox.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A biphasic effect of TNF-α in regulation of the Keap1/Nrf2 pathway in cardiomyocytes

Abstract: Antagonizing TNF-α signaling attenuates chronic inflammatory disease, but is associated with adverse effects on the cardiovascular system. Therefore the impact of TNF-α on basal control of redox signaling events needs to be understand in more depth. This is particularly important for the Keap1/Nrf2 pathway in the heart and in the present study we hypothesized that inhibition of a low level of TNF-α signaling attenuates the TNF-α dependent activation of this cytoprotective pathway. HL-1 cardiomyocytes and TNF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 55 publications
(65 reference statements)
0
40
0
Order By: Relevance
“…RNA was isolated from Induced Pluripotent Stem cells (iPSC), and iPS-derived cardiomyocytes using RNeasy mini kit (Qiagen, 74106). Cells were lysed using RLT lysis buffer and total RNA was isolated (33). RNA concentration and purity was measured using Thermofisher Nanodrop One c .…”
Section: Methodsmentioning
confidence: 99%
“…RNA was isolated from Induced Pluripotent Stem cells (iPSC), and iPS-derived cardiomyocytes using RNeasy mini kit (Qiagen, 74106). Cells were lysed using RLT lysis buffer and total RNA was isolated (33). RNA concentration and purity was measured using Thermofisher Nanodrop One c .…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, its most well-studied role in mammals is as the primary inflammatory cytokine, released by macrophages and other immune cells, and triggering the release of other cytokines, acting as a chemoattractant, stimulating phagocytosis, and promoting other inflammatory responses (Bradley, 2008;Sedger & McDermott, 2014). To our knowledge, however, it has not previously been shown to have trophic activity, protecting cells in the nervous system from stress-induced damage, although a link with the Nrf2/ Keap1 redox pathway in cardiomyocytes provides an interesting parallel (Shanmugam et al, 2016).…”
Section: ª 2020 the Authorsmentioning
confidence: 99%
“…In monocytes, TNF-α induced sustained nrf2 activation and increased expression of nrf2 targeted genes (25). Besides, low concentration of TNF-α evoked signi cant nuclear translocation of nrf2 and transactivation of nrf2 targets (26). Here, it was found that TNF-α not only upregulated nrf2 expression but also triggered nrf2 nuclear translocation, indicating that increased TNF-α level in RA patients might account for the nrf2 overexpression in the RA synovium.…”
Section: Discussionmentioning
confidence: 65%